PEWILAYAHAN AGROKLIMAT TANAMAN NILAM (Pogostemon spp.) BERBASIS CURAH HUJAN DI PROVINSI LAMPUNG (AGROCLIMATE ZONING OF PATCHOULY (Pogostemon ssp.) BASED ON RAINFALL IN LAMPUNG PROVINCE) - I. G. Darmaputra; Y. Koesmaryono; I. Santoso (Agromet, 2006)
The research purposed to determine the patchouly cropping in Lampung Province based on the agroclimate feasibility of area rainfall and to determine the monthly rainfall probability which less than the patchouly requirement. There are four steps on this research such as to determine the seasonal rainfall distribution by Principle Component Analysis, seasonal rainfall zoning by Cluster Analysis, and agroclimate zoning of patchouly by superimpossed annual region rainfall map, regional map of wet month, topography map to patchouly agroclimate requirement, and to determine the monthly rainfall probability which less than the patchouly crop requirement. The result of research shows 2,069,005 ha of Lampung Province area most feasible and feasible to patchouly cropping, which are spread in Lampung Barat Regency (15.7%), Lampung Tengah Regency (15.5%), Way Kanan Regency (14.3%), Tanggamus Regency (14%), Lampung Utara Regency (12.5%), Lampung Timur Regency (10.8%), Tulang Bawang Regency (8.5%), Lampung Selatan Regency (8.2%), Bandar Lampung City (0.4%) and Metro City (0.1%). The results also reveal that the seasonal rainfall in Lampung Province can be grouped in seven types (I-VII), and the most feasible area lay on type I-IV, but for feasible area lay on type I-VI. Related to rainfall probability, at type I there is not occured monthly rainfall ≤ 200 mm with probability ≥ 60%, where as at type II the condition can be occurred 5 months, at type III and IV occurred 4 months, and at type V and VI occurred 7 months.